2000
DOI: 10.1021/ja001109+
|View full text |Cite
|
Sign up to set email alerts
|

Standard Enthalpies of Formation of Fullerenes and Their Dependence on Structural Motifs

Abstract: Accurate standard enthalpies of formation of 115 isolated pentagon rule (IPR) fullerenes with 60-180 carbon atoms have been derived from energies of isodesmic interconversion reactions computed at the B3LYP/6-31G* level of theory. The calculated values of ∆H°f, which may serve as benchmarks for both calorimetric measurements and less sophisticated theoretical studies, are reproduced within 3 kcal/mol by a simple scheme based upon counts of 30 distinct structural motifs composed of hexagons together with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 41 publications
(64 reference statements)
11
136
0
Order By: Relevance
“…New puzzles also arise, especially when comparing the relative dissociation energies of various size fullerenes with each other [14,15]. For example, D(C 80 + ) was found [15] and confirmed independently [14] to be larger than D(C 78 + ) and D(C 82 + ), pointing out the higher stability of C 80 in comparison to its neighbors, in disagreement with earlier experimental studies [5], abundance spectra [14] and theoretical considerations based on heats of formation [17]. Further, the main C 78 and C 82 isomers were isolated and characterized in 1991 [18] and 1992 [19,20], respectively, shortly after Krätschmer et al proposed a method of synthesis, separation and purification of fullerenes in large quantities [21], whereas the D 2 isomer of C 80 was only isolated in 1996 [22], presumably because of its very low concentration in the mixture of isomers formed during arc-discharge fullerene synthesis.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…New puzzles also arise, especially when comparing the relative dissociation energies of various size fullerenes with each other [14,15]. For example, D(C 80 + ) was found [15] and confirmed independently [14] to be larger than D(C 78 + ) and D(C 82 + ), pointing out the higher stability of C 80 in comparison to its neighbors, in disagreement with earlier experimental studies [5], abundance spectra [14] and theoretical considerations based on heats of formation [17]. Further, the main C 78 and C 82 isomers were isolated and characterized in 1991 [18] and 1992 [19,20], respectively, shortly after Krätschmer et al proposed a method of synthesis, separation and purification of fullerenes in large quantities [21], whereas the D 2 isomer of C 80 was only isolated in 1996 [22], presumably because of its very low concentration in the mixture of isomers formed during arc-discharge fullerene synthesis.…”
Section: Introductionmentioning
confidence: 83%
“…The combination of the Becke three-parameter (B3) hybrid functional [38] with the Lee-Yang-Parr (LYP) correlation functional [39], together with the 3-21G basis set [40] was shown to yield reliable results for fullerenes [13,17,28,41]. Further, extension of the basis set from 3-21G to 6-31G* was shown not to significantly affect the resulting D(C 60 ) [13] and D(C 80 ) [31] values.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Additionally, thermochemical calculations have shown that the heats of formation for C 60 and C 70 may be significantly greater than other carbon molecules of similar size [55] indicating that an enormous amount of energy is being stored in the delocalized a-bond system. The enthalpies of formation for many fullerene molecules have also been calculated by various investigators resulting a fairly large database of thermodynamic values [56,57]. These results indicate that fullerenes are more stable than neighboring clusters which would be expected from their spherical nature.…”
Section: Fullerene Properties and Reactivitymentioning
confidence: 90%
“…[29]. The nucleus-independent chemical shifts (NICS) [30] at the cage centers, which have essentially the same values as the endohedral helium chemical shifts, were computed at the GIAO-SCF/3-21G level with the B3LYP/6-31G* geometries.…”
Section: Computational Detailsmentioning
confidence: 99%